COMBINATION OF PRIMARY AND SECONDARY PARTS (In the example of the works of Azod Sharafiddinov) (Scientific journal of the Fergana State University, 2025)
Azod Sharafiddinov was one of our scholars who embodied a number of examples, such as the example of wisdom, the example of courage, the example of ambition, and the example of ingenuity. O.Sharafiddinov wrote hundreds of articles, reviews and comments during his lifetime. In the growth of Uzbek literature, the contribution of critical works to the discovery of talented poets and writers, to the development of the skills of creators, to the emergence of a full-fledged character is huge. The scientist chose the way of summarizing his articles and reviews - creating large-scale scientific theoretical studies and perfect literary portraits, and his article-portraits occupy a unique place in the creation of portraits of mature artists. The portraits created by the critic are distinguished by their uniquely attractive, juicy language. In particular, in his writings, there is a special place for conjunctive clauses, that is, conjunctive possessives and participles, as well as secondary clauses. For this reason, in this article, we will try to analyze with the help of examples the meeting of combined possessives and participles and secondary parts in the works of O. Sharafiddinov.